SPATIAL TRANSFORMATION OF STRUCTURAL ELEMENTS OF MODERN COATINGS SHELLS (Collection of scientific works «Modern structures of metal and wood», 2020)
Currently, the principles of adaptive architecture are most often used in the practice of building unique large-span spatial shell coverings. Constructed buildings and structures acquire artificial intelligence for economical and comfortable operation and can use computer programs to respond to changing environmental conditions. Such buildings and structures consist of structural systems capable of transforming to meet the needs of operation. The particular complexity of the design of transformable spatial structural systems is that their design scheme changes significantly during operation, and all numerous extreme changes must be predicted in advance. Structures that can change their geometric dimensions, that is, transform during operation, are considered  in  the  article  to  solve  the  problems  of  adaptive  architecture  to  create  the  proper microclimate inside buildings and structures. Only  spatial  structures  consisting  of  elements  of  complex  displacement  in  space  were identified  in the research, although there  are  many  constructed transformable  shells of coverings with a simpler transformation in space (horizontal, around a vertical axis, along the guiding support elements of the surface of the transfer shells). The  development  of  such  structures  has  many  directions.  One  of  the  most  difficult  is  the development of  mobile structures in the space  industry, when a  large-sized structure packed in a container of minimum dimensions is delivered into orbit, and in orbit it automatically opens to the required dimensions. Modern  approaches  to  the  transformation  of  structures  are  given,  which  were  highly appreciated during the new construction, reconstruction and operation of buildings and structures, and are promising for further research and application. For examples, spatial shell structures were used, as well as those operation and construction of which are carried out using computer programs. The analysis of the constructed shells of various shapes using pneumatic formwork to obtain mathematical models to determine the optimal overall dimensions and use in the design.